2019
DOI: 10.3390/ijerph16183421
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Demands in Basketball Referees during the U-16 European Women’s Championship

Abstract: (1) Background: The use of advanced technology to study the energy demands of sport participants during actual sport competition is an important current research direction. The purpose of this study was to identify the physiological, internal, and external demands placed on basketball referees using ultra-wideband (UWB) technology, in relation to the period of the game. (2) Methods: The sample was comprised of nine international referees, and the data collection took place during the Women’s EuroBasket Sub-16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
2
24
1
3
Order By: Relevance
“…This hypothesis was fully confirmed. The results obtained agree with the studies that the degree of general preparedness of the arbiters is determined by the level of physical fitness, the level of theoretical training, the level of psychological training, the level of practical training, personal characteristics (type of temperament) [16][17][18]. The research showed that the results of testing physical and functional readiness among the referees of the experimental group increased.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis was fully confirmed. The results obtained agree with the studies that the degree of general preparedness of the arbiters is determined by the level of physical fitness, the level of theoretical training, the level of psychological training, the level of practical training, personal characteristics (type of temperament) [16][17][18]. The research showed that the results of testing physical and functional readiness among the referees of the experimental group increased.…”
Section: Discussionsupporting
confidence: 88%
“…The Local Positioning System was installed on the futsal pitch where the team played their matches in concordance to user manual and previous studies [10,23]. The distribution of six antennas ( Figure 1) with UWB technology were fixed 5 m from the perimeter line of the field, except for those located at the middle line of the field, which were fixed 7 m from the perimeter.…”
Section: Methodsmentioning
confidence: 99%
“…The reference system is composed of six antennas that are transmitters and receivers of the radio frequency signal. The antennas (mainly the master antenna) perform the computerizing of the position of the devices that are in their area of performance, while the devices receive that calculation [ 10 ], the radio frequency signal is almost under the same principle as the GPS system [ 22 , 23 ]. The validity and accuracy of this type of LPS has been demonstrated exposed in reference to determining distance covered, speed, mean velocity, accelerations and decelerations for intermittent activities [ 10 , 11 , 13 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value represents the sum of the vector of G-forces the skier experienced in the vertical, antero-posterior, and medio-lateral axes. The impact value was registered when the G-forces of the movement exceeded 5 g [ 18 , 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%